Fertility Performance and Obstetric Outcomes Among Women With Previous Cesarean Scar Pregnancy - Ron Maymon; Ran Svirsky; Noam Smorgick; Sonia Mendlovic; Reuvit Halperin; Karin Gilad; Yosef Tobvin (2011)
The purpose of this study was to assess fertility performance and obstetric outcomes after treatment of cesarean scar pregnancy.We conducted a retrospective study in a large tertiary hospital in Israel. The study included 18 women with a diagnosis of cesarean scar pregnancy between 2000 and 2009.The incidence of cesarean scar pregnancy among our parturient patients was 1 per 3000 for the general obstetric population and 1 per 531 among those with at least 1 cesarean delivery. Sixteen were treated primarily with methotrexate. Two were treated primarily by surgery, and 2 more were treated by surgery after failed methotrexate treatment. After cesarean scar pregnancy treatment, 7 women conceived spontaneously, and 1 conceived by in vitro fertilization-intracytoplasmic sperm injection. The remaining 10 (55%) did not wish to conceive again. Two of the women who became pregnant (25%) had recurrent cesarean scar pregnancy.This study shows encouraging results for fertility performance and obstetric outcomes after treatment of cesarean scar pregnancy. Nevertheless, the risk of recurrent cesarean scar pregnancy is not negligible.